Validation of the Arabic Version of General Medication Adherence Scale (GMAS) in Sudanese Patients with Diabetes Mellitus - Mahmoud MA; Islam MA; Ahmed M; Bashir R; Ibrahim R; Al-Nemiri S; Babiker E; Mutasim N; Alolayan SO; Al Thagfan S; Ahmed SBM; Sales I; et al. (Dove Medical Press, 2021)
Mansour Adam Mahmoud,1 Md Ashraful Islam,2 Malaz Ahmed,3 Randa Bashir,3 Romisa Ibrahim,3 Shahd Al-Nemiri,3 Ethar Babiker,3 Neven Mutasim,3 Sultan Othman Alolayan,1 Sultan Al Thagfan,1 Samrein BM Ahmed,4 Ibrahim Sales,5 Mohamed Azmi Hassali6 ,† Yaser Alahmadi,1 Mirghani A Yousif3 1Department of Clinical & Hospital Pharmacy, College of Pharmacy, Taibah University, Al-Madinah Al-Munawarah, Saudi Arabia; 2Department of Pharmacy Practice, College of Clinical Pharmacy, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 3Department of Clinical Pharmacy & Pharmacy Practice, Faculty of Pharmacy, University of Gezira, Wad Madani, Sudan; 4College of Medicine, University of Sharjah, Sharjah, United Arab Emirates; 5Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 6Discipline of Social and Administrative Pharmacy, School of Pharmaceutical Sciences, Universiti Sains Malaysia, Penang, Malaysia†Mohamed Azmi Hassali passed away on July 16, 2021Correspondence: Mansour Adam MahmoudDepartment of Clinical and Hospital Pharmacy, College of Pharmacy, Al-Madinah Al-Munawarrah, Saudi ArabiaEmail Mammm.99@gmail.comObjective: The aim of this study was to validate the Arabic version of General Medication Adherence Scale (GMAS) in Sudanese patients with type 2 diabetes mellitus (T2DM).Methods: A 3-month cross-sectional study was conducted among patients with T2DM at Al-Daraja Health Center, located in Wad Medani, Sudan. A convenient sample of patients was selected, and the study sample size was calculated using the item response ratio. Factorial, known group, and construct validities were determined. Internal consistency and reliability were also determined.Results: Responses were provided by 500 patients. The average medication adherence score was 30 (median 31). The normed fit index (NFI) was 0.950, the comparative fit index (CFI) was 0.963, the incremental fit index (IFI) was 0.963, and the root-mean-square error of approximation (RMSEA) was 0.071. The results from these fit indices indicated a good model. Factorial, known group and construct validities were all established. A significant association was found between adherence score and age (P = 0.03) since a larger proportion of older patients were found to have high adherence compared to patients in other age groups. The reliability (α) of the questionnaire was 0.834.Conclusion: The Arabic version of GMAS was validated in Sudanese patients with T2DM making it a suitable scale to be used in this population.Keywords: medication adherence, patient compliance, medication persistence, chronic illness, Sudan